(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
Small and medium enterprises (SMEs) in Tanzania face persistent challenges despite their critical role in economic development. While prior research has examined individual strategic orientations, little is known about their combined influence on different managerial functions in emerging economies. This study investigates the synergistic effects of technology orientation (TO), entrepreneurial orientation (EO), and market orientation (MO) on small business success across four managerial domains: marketing, operations, human resource, and financial management. Using a positivist paradigm and quantitative approach, data were collected from 410 randomly selected SMEs across eight Tanzanian regions and analyzed through multiple regression with validity and reliability assessments. The results reveal distinct patterns of influence. Technology orientation emerged as a consistent positive predictor across all domains, with the strongest effect on HRM (β = 0.470), suggesting digital tools enhance employee management in resource-constrained settings. Entrepreneurial orientation significantly predicted marketing (β = 0.443), operations (β = 0.302), and financial performance (β = 0.493) but showed a negative association with HRM (β = -0.083), indicating potential trade-offs between entrepreneurial dynamism and structured people management. Market orientation positively influenced marketing (β = 0.172), operations (β = 0.346), and HRM (β = 0.413) but had no significant effect on financial management (β = 0.002), suggesting customer focus improves internal processes but may yield delayed financial returns in competitive markets. Collectively, these orientations explain substantial variance in business success: 58.6% in marketing, 58.8% in operations, 58.3% in HRM, and 48.1% in financial management. The study contributes to strategic orientation theory by demonstrating context-dependent effects in an emerging African economy, revealing trade-offs between entrepreneurial dynamism and HR management, and highlighting the delayed financial returns of market orientation. It offers practical guidance for Tanzanian SMEs to achieve sustainable growth through balanced integration of these strategic orientations.